La tutela degli animali utilizzati a fini scientifici e il diritto alla ricerca: la delicata valutazione dei danni e dei benefici compiuta dall’autorità competente (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The implementation of Directive 2010/63/EU, on the protection of animals used for scientific purposes, sees the difficult combination and balance between the right to health, the right to research, the right to education and environmental protection with the opposing interest to the protection of animals. The limits and guarantees of these rights are established by hyper-technical legislation whose culmination is represented by the authorization power granted to the Ministry of Health (competent authority pursuant to Article 4, paragraph 5 of Legislative Decree 26 / 2014). Specifically, the point of equilibrium between the opposing interests translates into the release or refusal to carry out a research project at the end of an evaluation process that presents aspects that are not always linear.
Keywords: Research; protection; animals; damages; benefits